EVALUATING THE EFFECTIVENESS OF THE MERDEKA CURRICULUM IN SCIENCE LEARNING ON JUNIOR HIGH SCHOOL STUDENTS’ SCIENTIFIC LITERACY - Rifqi Ardiyansyah; Novi Ratna Dewi (SPEKTRA: Jurnal Kajian Pendidikan Sains, 2026)
This study aims to evaluate the effectiveness of the Merdeka Curriculum in science education on the scientific literacy skills of junior high school students. The study uses an evaluative approach with the CIPP (Context, Input, Process, Product) model, with a primary focus on the product aspect that reviews the achievements and impact of learning on students' scientific literacy. Quantitative data were obtained through scientific literacy tests, while qualitative data were collected through teacher questionnaires. Quantitative data analysis was performed using the Wilcoxon Signed Rank Test with an ideal criterion value of 84. The results showed that students' scientific literacy scores were still statistically below this criterion value. The average percentage of student scientific literacy achievement was in the range of 36-40%, which falls into the nominal scientific literacy category. These findings indicate that students are still limited to the introduction of basic science concepts and are not yet fully able to apply and evaluate these concepts in real-life contexts. Although teachers perceive an increase in learning outcomes and scientific literacy after the implementation of the Merdeka Curriculum, this increase is not yet optimal. Therefore, it is necessary to strengthen the implementation of contextual and project-based learning so that the goal of increasing scientific literacy can be achieved more effectively.